A Guy Thing - Koch, Chris; Scarwid, Diana; James Brolin; Lochlyn Munro; Selma Blair; Shawn Hatosy; Jason LeeJulia Stiles (USA Metro-Goldwyn-Mayer (MGM), 2003)
When he wakes up the morning after his bachelor party in bed with a strange woman (Stiles), a man (Lee) presumes he must have cheated on his fiancee. Guilt leads him to try to cover it up in the week before the wedding, high jinks ensue.
When a man wakes up the morning after his bachelor party in bed with a strange woman he presumes he must have cheated on his fiancee.
Greg Glienna
Languages : English, Czech Subtitles : English, Turkish, Slovenian
Keywords: Romance; Comedy